2016
DOI: 10.1016/j.fertnstert.2016.07.1095
|View full text |Cite
|
Sign up to set email alerts
|

Delayed blastulation, multinucleation, and expansion grade are independently associated with live-birth rates in frozen blastocyst transfer cycles

Abstract: The blastocyst expansion grade after warming was predictive of successful outcomes independent of the inner cell mass or trophectoderm score. Delayed blastulation and multinucleation were independently associated with lower live-birth rates in frozen cycles. Implantation potential of the frozen blastocysts available should be included in the decision-making process regarding embryo number for transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 38 publications
9
73
0
1
Order By: Relevance
“…The final inclusion was 13 studies that met the selection criteria for our meta‐analysis. Hence, 23 studies were included in the following meta‐analyses . The main characteristics and assessment for risk of bias of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The final inclusion was 13 studies that met the selection criteria for our meta‐analysis. Hence, 23 studies were included in the following meta‐analyses . The main characteristics and assessment for risk of bias of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, 23 studies were included in the following meta-analyses. 4,6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The main characteristics and assessment for risk of bias of the included studies are presented in Table 1.…”
Section: Results Of the Searchesmentioning
confidence: 99%
See 2 more Smart Citations
“…The three morphological defects, which we evaluated by TLS, were not different between positive and negative chemical and clinical pregnancies and live birth. In contrast, other studies reported the negative impact of DC as well as MN on implantation rate (Desai et al, ; Goodman et al, ) and birth outcome (Desai et al, ; Desch et al, ).…”
Section: Discussionmentioning
confidence: 86%